1999
DOI: 10.1016/s0921-4488(98)00130-8
|View full text |Cite
|
Sign up to set email alerts
|

Application of two models to the lactation curve of Massese ewes

Abstract: The experiment was carried out on 52 lactations of 37 multiparous Massese ewes. Milk yield was recorded weekly, starting before the 15th day from lambing. Due to the mating practice of the breed, three types of lactation were detected: Type 1, a short lactation initiated in autumn; Type 2, a short lactation initiated in spring, following the Type 1 lactation; Type 3, a long lactation initiated in autumn. The Wood model (W) and a bi-exponential function (CB) were applied to ®t milk yield data of individual lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
2
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 10 publications
2
16
2
1
Order By: Relevance
“…Nevertheless, the duplicated alleles might have negative pleiotropic effects represented by reduced fecundity and greater seasonality in reproduction as evidenced in Icelandic sheep for the A Wt allele or by decreased fertilization rate as reported for a grey allele (Adalsteinsson, 1970 and1975). Massese sheep are characterized by a partial seasonality of oestrus, which can occur at any time during the year (Franci et al, 1999), and this trait could be due to the usual black coat colour that might exclude or maintain in heterozygosity the duplicated copy allele(s) with putative negative effects when homozygous. Further studies are needed to evaluate the effects of ASIP alleles on production and reproduction traits in the Massese breed.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the duplicated alleles might have negative pleiotropic effects represented by reduced fecundity and greater seasonality in reproduction as evidenced in Icelandic sheep for the A Wt allele or by decreased fertilization rate as reported for a grey allele (Adalsteinsson, 1970 and1975). Massese sheep are characterized by a partial seasonality of oestrus, which can occur at any time during the year (Franci et al, 1999), and this trait could be due to the usual black coat colour that might exclude or maintain in heterozygosity the duplicated copy allele(s) with putative negative effects when homozygous. Further studies are needed to evaluate the effects of ASIP alleles on production and reproduction traits in the Massese breed.…”
Section: Discussionmentioning
confidence: 99%
“…The ®rst record occurred between 8±15 days from lambing when the newborns were separated from their mothers. As described in a previous paper (Franci et al, 1999) the ®rst 37 lambings occurred in autumn (September± November), after which all the ewes were again continuously exposed to mating, according to the usual breeding system with Massese, that leaves the ram in the¯ock year-round. Fifteen ewes then conceived and lambed again in March±April, after a dryoff period of about one month.…”
Section: Methodsmentioning
confidence: 98%
“…An earlier study (Franci et al, 1999) on the application of non-linear models for these milk yields showed that peak production was very early, at an average of 10 days postpartum. Since the present study, which is mainly concerned with milk quality variables, did not consider any control during the ®rst week postpartum, as instead was done in the earlier paper (Franci et al, 1999), it was decided to use a linear model (a third degree regression) to study milk yield as well.…”
Section: Effect Of Type Of Lactation and Stage Of Lactation On Milk Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Building of curves by using Wood's model and their correction by using a non-linear modification, is recommended in this case (Cappio-Borlino et al, 1995). This gives better results and more accurately reflects the performances of milk production during lactation (Portolano et al, 1996;Todaro et al, 1997;Franci et al, 1999). Goodness of fit statistics of the three model curves had high values (R 2 = 0.89, 0.86, 0.82 for Alpine breed, crossbreed and local breed, respectively).…”
Section: Cappio-borlino First Lactation Curvesmentioning
confidence: 99%